CVD growth of thermoelectric semiconductor for energy conversion - Ng, Bok Wei. (2011)
This project was to investigate the performance of InSb synthesized by CVD technique in lithium-ion batteries. The purpose was to discuss and determine the suitable parameters such as temperature, distance, mass flow rate and reaction time which meet the criteria such as uniform morphology, 1:1 InSb composition and InSb phase for electrochemical measurement. After synthesizing the samples, they will be characterised by using FESEM, SEM and XRD and their results compared. Four experiments were repeated for electrochemical measurement as they had met the criteria. And based on the electrochemical measurement results, R4 InSb electrode had a better and stable performance as compared to the other three InSb electrodes where the discharge capacity is in relatively constant value between 210mAh/g and 230mAh/g for 50 cycles between 0.5V to 1.2V. This experiment was repeated again for further measurement up to 100 cycles between 0.001V to 1.2V. The results for this experiment showed that the discharge capacity was 326mAh/g for 100 cycles, and had a cycle-retention of 57.4%. The CV that had been done showed that the excellent performance depended on the reversible lithium insertion/indium extrusion reaction with LiyIn1-ySb framework.